Prognostic significance of left ventricular functional parameters in relation to infarct location after ST-elevation myocardial infarction. (3rd October 2022) - Tiller, C; Holzknecht, M; Lechner, I; Reindl, M; Fink, P; Mayr, A; Klug, G; Brenner, C; Bauer, A; Metzler, B; Reinstadler, S J
Abstract: Aims: In survivors of ST-elevation myocardial infarction (STEMI), the impact of infarct location on the prognostic significance of left ventricular functional parameters is not well established. The aim of this study was to investigate the prognostic relevance of left ventricular (LV) functional parameters in relation to infarct location in STEMI patients treated with contemporary primary percutaneous coronary intervention (PCI). Methods: This observational study analyzed 803 patients with STEMI that underwent a cardiac magnetic resonance imaging scan in median 3 (interquartile range [IQR]: 2–5) days after primary PCI. The following LV functional parameters were evaluated: LV ejection fraction, LV global longitudinal strain, fast manual long-axis strain (LAS) and mitral annular plane systolic excursion (MAPSE). Primary endpoint was the occurrence of major adverse cardiac events (MACE) defined as composite of death, re-infarction and congestive heart failure. Results: Three hundred and sixty nine patients (46%) had anterior STEMI. These patients had lower LV functional parameters including LV ejection fraction (p<0.001), LV global longitudinal strain (p<0.001), LAS (p<0.001) and MAPSE (p<0.014). MACE was evaluated at a median of 13 (IQR: 12–37) months after STEMI and occurred in 78 patients (10%). In receiver operating curve analysis, the predictive value of LV ejection fraction, LV global longitudinal strain, LAS and MAPSE was 0.59 (p=0.013), 0.64 (p<0.001), 0.67 (p<0.001) and 0.66 (p<0.001), respectively. When divided according to infarct location, MACE occurred in 47 (13%) anterior STEMI patients, and in 31 (7%) non-anterior STEMI patients, respectively. Area under the curve for the prediction of MACE in anterior vs. non-anterior STEMI was 0.59 vs 0.55 for LV ejection fraction, 0.61 vs 0.63 for LV global longitudinal strain, 0.69 vs 0.62 for LAS and both 0.66 for MAPSE. In multivariable analysis, LAS was independently associated with an increased risk of MACE (hazard ratio: 1.20; 95% confidence interval: 1.10–1.30; p<0.001) in anterior STEMI, whereas in non-anterior STEMI, LV global longitudinal strain was an independent predictor of MACE (hazard ratio: 1.22; 95% confidence interval: 1.08–1.38; p=0.002). Conclusion: Fast manual LAS emerged as independent predictor of MACE in anterior STEMI treated with contemporary primary PCI whereas LV global longitudinal strain was independently associated with MACE in non-anterior STEMI. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Austrian Society of Cardiology